Maillard reaction products with furan ring, like furosine, cause kidney injury through triggering ferroptosis pathway. (30th July 2020) - Li, Huiying; Yang, Huaigu; Li, Peng; Li, Ming; Yao, Qianqian; Min, Li; Zhang, Yangdong; Wang, Jiaqi; Zheng, Nan
Highlights: Furosine widely exists in heated foods and could cause kidney damage. MRPs with furan ring cause renal damage by activating ferroptosis in renal cells. Aldose reductase was proved to be the direct target of furosine in renal cells. Abstract: Maillard reaction products (MRPs), produced in the heating of food, might pose adverse effects on human health. As a classical MRP, the toxicity of furosine in kidney tissue was evaluated and the related mechanism was investigated here. We detected the concentration of furosine in mouse serum and organs using ultra-high-performance liquid chromatography, and screened out phosphatidylethanolamine (PE; 18:0/16:1) as the special metabolite in kidney by metabonomics analysis. Furthermore, furosine was verified to induce ferroptosis in kidney cells by quantitative real-time RT-PCR (q-PCR) and western blotting. The affinity between furosine and aldose reductase (AR) was measured by surface plasmon resonance (SPR), indicating AR is one of the targets of furosine. In addition, the furan ring was shown to be the main active group via structure–activity relationship (SAR) studies of furosine and other MRPs, which were toxic to kidney cells by activating ferroptosis pathway.